EVALUASI STABILITAS LERENG YANG TELAH DIPERKUAT PADA JALAN TOL SEMARANG – SOLO SEKSI V UNGARAN BAWEN - Khrisna, Rama Harya; Atmanto, Indrastono Dwi; Wibowo, Hardi (Jurnal Karya Teknik Sipil, 2013)
Semarang – Solo toll roads, Ungaran Bawen Section was built to support economic growth in Semarang – Solo and its surroundings. The road across the hills and valleys that contain clay shale. Catastrophic landslide and slope occurs in toll roads at Semarang – Solo STA 19+525. This undergraduate thesis is about the stability of slopes on toll roads, mechanisms and mitigation. The analysis involves conditions which the motions of the soil on the slope because of slope unstability, manual calculation slope stability with Fellenius methods, geotechnical analysis and the use of retaining wall as an alternative method of reinforcement. Geotechnical analysis using Plaxis finite element software. Plastic and elastic model of Mohr-Coulomb failure criterion was chosen as a model soil. Analysis showed that the most optimum avalanche  mitigation is to install a retaining. By using retaining wall combine, minimum slope safety factor be increased and reached 1,541.